An Example of Travertine Formations in the Ilıca Segment of the Eastern Anatolian Fault Zone: Elmalı (Bingöl) Travertine - Erol, Serap Çolak; Aksoy, Ercan (My University, 2025)
The travertine formation subject to the study is located in the near northeast of Elmalı Village (Bingöl) located at approximately 28th km of Bingöl-Karlıova highway on the Ilıca segment, which is one of the important segments of the left-lateral strike-slip East Anatolian Fault Zone, which is the second largest neotectonic structure in Turkey. The outcrops of Paleozoic-Mesozoic Bitlis Metamorphites, which play a source rock role in travertine formation, are mostly characterized by marbles around Bingöl. It is thought that Solhan Volcanics, which are mainly composed of pyroclastic rocks, play a cap rock role that maintains this temperature. Ca and Mg concentrations in the samples are the highest elements with 396226 ppm and 2713.84 ppm, respectively. From stable isotope analyses, ?13C values range from +7.7 to +11.2 (‰ PDB); ?18O values are between -9.8 and -11.7 (‰PDB). U-Th age data obtained from the samples indicate that travertine deposition started at least 69672 years ago.
Keywords: Bingöl; travertine; The East Anatolian Fault Zone; Ilıca segment; U-Th age analysis